Estudio de emisiones contaminantes producidas por un motor MEP con transmisión automática y transmisión manual - Noroña Merchan, Marco Vinicio (2018)
In this study we compare the contaminant emissions produced be an engine with triggered ignition, the first one with a manual transmission and the second one with an automatic transmission. For this study we have selected a Chevrolet vehicle model SZ with 2000 cm3 cylinders used in an altitude of 2800 meters over sea level, considering that this altitude has a notable effect in the formation of contaminant gases because this variable modifies the thermodynamic cycle of operation and the combustion conditions. Two different tests were conducted; a stationary test and a test in route considering the test protocols that are established by the Technological Transference Center for Training and Research of Vehicles Emissions (CCICEV). The results obtained by this investigation revealed that a vehicle with automatic transmission produces less quantity of contaminant emissions in the stationary test and in test in route than the same vehicle with manual transmission. There are polluting gases that are reduced in a high percentage with respect to the mechanical box when an automatic is used.